2020
DOI: 10.1002/edm2.151
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between triglyceride glucose index, retinopathy and nephropathy in Type 2 diabetes

Abstract: Aims To explore the relationship between TyG index, diabetic retinopathy (DR) and nephropathy. Methods This was a cross‐sectional observational study that examined 1413 subjects with type 2 diabetes (both known and newly diagnosed). Subjects underwent a detailed standard evaluation to detect diabetic retinopathy (fundus photography) and nephropathy (defined as urinary albumin excretion ≥ 30 mg/24 h). The TyG index was calculated as ln (fasting triglycerides (mg/dL) × fasting glucose (mg/dL)/2) and stratified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 39 publications
4
32
1
Order By: Relevance
“…Several studies suggested that TyG index plays a role in nephric microvascular damage. Srinivasan S et al ( 43 ) showed a higher TyG index was associated with the presence of retinopathy and nephropathy in individuals with diabetes and could be used for monitoring metabolic status in clinical settings. Liu et al ( 44 ) showed the TyG index was independently associated with DN in patients with type 2 diabetes, and was a better marker than HOMA2-IR for the identification of DN in type 2 diabetes patients in a cross-sectional study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that TyG index plays a role in nephric microvascular damage. Srinivasan S et al ( 43 ) showed a higher TyG index was associated with the presence of retinopathy and nephropathy in individuals with diabetes and could be used for monitoring metabolic status in clinical settings. Liu et al ( 44 ) showed the TyG index was independently associated with DN in patients with type 2 diabetes, and was a better marker than HOMA2-IR for the identification of DN in type 2 diabetes patients in a cross-sectional study.…”
Section: Discussionmentioning
confidence: 99%
“… 21 A high TyG index is associated with the presence of retinopathy and nephropathy in individuals with diabetes and can be used for monitoring metabolic status in clinical settings. 22 , 23 In addition, a high TyG index is associated with an increased risk of microalbuminuria, and TyG can effectively identify individuals at risk of non-alcoholic fatty liver disease (NAFLD) since it is highly sensitive to the detection of NAFLD subjects, and can be suitable as a diagnostic standard for Chinese adults with NAFLD. 24 , 25 Previous studies have confirmed that vitamin D is independently related to IR in patients with T2DM, but the study applied HOME-IR to reflect insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The TyG index, derived from FBG and TG, was proven to be a reliable and simple surrogate for metabolic syndrome and IR [18]. Mounting evidence has proved the crucial value of TyG index in predicting diabetic complications in patients with T2DM [19][20][21]. Study by Liu et al showed a signi cant association between TyG index and the risk of diabetic nephropathy in 682 adult patients with T2DM [22].…”
Section: Discussionmentioning
confidence: 99%